2019
DOI: 10.1016/j.jaad.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab treatment is associated with decreased systemic and vascular inflammation in patients with moderate-to-severe psoriasis: Feasibility study using 18F-fluorodeoxyglucose PET/CT

Abstract: Ustekinumab treatment was significantly associated with decreased systemic and vascular inflammation related to metabolic syndrome and cardiovascular disease among patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 23 publications
2
26
0
5
Order By: Relevance
“…At week 12, there was a significant (i.e., similar to statin effects) 18.65% decrease in AVI in patients treated with ustekinumab compared with placebo (Tawakol et al, 2013). This finding is proof of principle that antibody-based therapies can causally decrease AVI, and advances observations from prior uncontrolled studies, which showed an improvement in AVI in Korean patients with psoriasis treated with ustekinumab (Kim et al, 2019). Moreover, this finding appears specific to the IL-12 and IL-23 pathway, as similar trials by our group and others have shown a neutral effect of biologics that target TNF (adalimumab) and IL-17 (secukinumab), respectively (Bissonnette et al, 2017;Gelfand et al, 2019;Mehta et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…At week 12, there was a significant (i.e., similar to statin effects) 18.65% decrease in AVI in patients treated with ustekinumab compared with placebo (Tawakol et al, 2013). This finding is proof of principle that antibody-based therapies can causally decrease AVI, and advances observations from prior uncontrolled studies, which showed an improvement in AVI in Korean patients with psoriasis treated with ustekinumab (Kim et al, 2019). Moreover, this finding appears specific to the IL-12 and IL-23 pathway, as similar trials by our group and others have shown a neutral effect of biologics that target TNF (adalimumab) and IL-17 (secukinumab), respectively (Bissonnette et al, 2017;Gelfand et al, 2019;Mehta et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…However, one of these studies evaluated several biomarkers and found decreased levels of glycoprotein acetylation, a novel composite biomarker of systemic inflammation, in patients treated with adalimumab compared with those treated with phototherapy . Additionally, a small prospective study of ustekinumab in a Korean population observed significantly decreased vascular inflammation in individuals who achieved ≥ 75% improvement in PASI over a mean treatment period of 5 months . Ongoing prospective studies include Vascular Inflammation in Psoriasis (VIP) trials that are currently evaluating the effects of ustekinumab (VIP‐U; NCT02187172), secukinumab (VIP‐S; NCT02690701) and apremilast (VIP‐A; NCT03082729) on aortic inflammation as measured by 18 F‐FDG PET/CT and on levels of biomarkers associated with metabolic and cardiovascular risk.…”
Section: Goals For Treating Systemic Inflammation In Psoriasismentioning
confidence: 99%
“…57 Additionally, a small prospective study of ustekinumab in a Korean population observed significantly decreased vascular inflammation in individuals who achieved ≥ 75% improvement in PASI over a mean treatment period of 5 months. 58 Ongoing prospective studies include Vascular Inflammation in Psoriasis (VIP) trials that are currently evaluating the effects of ustekinumab (VIP-U; NCT02187172), secukinumab (VIP-S; NCT02690701) and apremilast (VIP-A; NCT03082729) on aortic inflammation as measured by 18 F-FDG PET/CT and on levels of biomarkers associated with metabolic and cardiovascular risk. Results from studies of biological agents in IMIDs other than psoriasis support the hypothesis that biological agents can reduce systemic inflammation and prevent cardiovascular damage.…”
Section: Goal 1: Prevent Damage Associated With Inflammation and Prevmentioning
confidence: 99%
“…Для препарата характерны низкая иммуногенность и достаточно благоприятный профиль безопасности. По данным международных регистров, устекинумаб характеризуется самым высоким показателем «выживаемости» терапии среди всех ГИБП [39,41]. До настоящего времени не было проведено прямых сравнительных клинических испытаний между устекинумабом и другими препаратами, одобренными для лечения болезни Крона (инфликсимабом, адалимумабом, цертолизумаба пэголом или ведолизумабом).…”
Section: целесообразность раннего назначения генноинженерных препаратовunclassified